2020
DOI: 10.1371/journal.pone.0232231
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and future risk of endometrial cancer in women with endometrial hyperplasia: A systematic review and meta-analysis

Abstract: BackgroundTo inform treatment decisions in women diagnosed with endometrial hyperplasia, quantification of the potential for concurrent endometrial cancer and the future risk of progression to cancer is required. MethodsWe identified studies up to September 2018 that reported on the prevalence of concurrent cancer (within three months of endometrial hyperplasia diagnosis), or the incidence of cancer, identified at least three months after hyperplasia diagnosis. Random-effects meta-analyses produced pooled esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 58 publications
(65 reference statements)
5
55
0
8
Order By: Relevance
“…Endometrial hyperplasia is a common gynecologic diagnosis, histologically defined as the presence of proliferation of the endometrial glands resulting in an increase in gland-to-stroma ratio [ 21 ]. It is also recognized as precursor lesion of endometrial cancer (endometrioid type).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial hyperplasia is a common gynecologic diagnosis, histologically defined as the presence of proliferation of the endometrial glands resulting in an increase in gland-to-stroma ratio [ 21 ]. It is also recognized as precursor lesion of endometrial cancer (endometrioid type).…”
Section: Discussionmentioning
confidence: 99%
“…It is also recognized as precursor lesion of endometrial cancer (endometrioid type). Doherty et al ., in their metanalysis, reported the risk of non-atypical hyperplasia progression to cancer at annual incidence rate at 2.6% and atypical hyperplasia at 8.2% [ 21 ]. Abnormal uterine bleeding is the most common symptom of endometrial hyperplasia and cancer [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, treatment for endometrial hyperplasia is more important in perimenopausal women. In the endometrial hyperplasia without atypia, the progression rate to cancer was reported 2.6% per year [ 26 ]. Therefore, the use of LNG-IUS, which is recognized as the most effective drug treatment, has numerous aspects to be considered as the first-line treatment.…”
Section: Endometrial Hyperplasiamentioning
confidence: 99%
“…The incidence of benign hyperplastic endometrial pathology in premenopausal women decreased 3.4-fold at the time close to menopause, due to a gradual reduction in menstrual function and the effect of sex-steroide hormones on cell proliferation in the endometrium. At the same time, the rate of detection of precancerous pathology and EC increased shortly before menopause, probably due to the accumulation of genomic alterations that affect the way cells differentiate and the mechanisms of elimination of transformed cells [2]. The data we obtained do not contradict the data of the National Cancer Registry of Ukraine over the last ten years that indicate that EC ranks 3 in the age structure of the disease among women aged 30-54 years and 2 in those aged 55-74 years [13].…”
Section: Objective Of the Studymentioning
confidence: 99%
“…Furthermore, the optimal treatment duration and follow-up regime for patients after completion of treatment has not been confirmed yet [1,7,15,16]. The rate of progression of EH to atypicality either with monitoring or with treatment by various types of progestins and varying durations of use has also not been measured; the data range from 5% over 20 years to 1.5-2% per year, which is already quite significant [2,4,8,10,17]. An ever-increasing number of reports of individual unsuccessful hormone therapy for non-atypical endometrial hyperplasia or progression of the disease even in the course of treatment [3] has prompted clinicians and researchers to look for new approaches to the management of this disease.…”
mentioning
confidence: 99%